A case of Huntington disease‐like 2 in a patient of African ancestry: the everlasting support of clinical examination in the molecular era. Issue 10 (6th October 2022) - Ruscitti, Federica; Origone, Paola; Rosti, Giulia; Trevisan, Lucia; Marchese, Roberta; Brugnolo, Andrea; Massa, Federico; Castellini, Paola; Mandich, Paola
Abstract: Chorea, cognitive decline, and psychiatric symptoms are shared by Huntington's disease (HD) and similar conditions called HD phenocopies. We describe the first case reported in Italy of Huntington disease‐like 2 (HDL2), clinically and radiologically indistinguishable from HD, showing the importance of considering African ancestry in the diagnostic process. Abstract : Given the strong clinical and radiological similarities between Huntington's disease (HD) and its phenocopies, we highlight the importance of a multidisciplinary clinical approach and the role of ethnicity in the diagnostic workout of chorea.